Frank O'Hara rebuilds the Seagram Building: a radical poetry of event. Issue 1 (2nd January 2016) - Finberg, Keegan Cook
Abstract : This essay brings together architectural discourse and literary studies to consider alternative possibilities within our understanding of Cold War politics. It examines poems that figure Mies van der Rohe's Seagram Building as important to a radical politics and experimentalism in Frank O'Hara's early poetry. The figured Seagram Building – steeped in architectural modernist ideologies and nationalist corporate interests – works to open the possibility for a new ethics of encounter within midtown New York City. Deriving a connection between O'Hara's 'I do this I do that poems' and the politics of architectural space shows the need for O'Hara's poems to be resituated. They are not poems that chronicle the city, but rather should be read as akin to contemporaneous event scores and happenings. Like Fluxus scores, this poetry problematises the difference between hermeneutics and enactment as it critiques dominant modernist notions of 'reading poetry' in general.